Novel design of serpentine channel heat sinks with rectangular and triangular ribs and grooves for 25Ah Li-ion battery thermal management - John Sathvik Sakkera; Ravikiran Chintalapudi; Bridjesh Pappula; Seshibe Makgato (International Journal of Thermofluids)
Efficient thermal management is crucial for high-capacity Li-Ion batteries used in electric vehicles and energy storage systems. The study presents and evaluates novel designs of Serpentine Channel Heat Sinks (SCHS) that integrate rectangular ribs with rectangular (RRRG) and triangular grooves (RRTG). These novel designs are specifically optimized for battery cooling, where maintaining consistent thermal performance is crucial for safety and durability. The present study investigates the influence of groove geometry on fluid dynamics and heat transport, in contrast to traditional designs. This work evaluates thermal performance, including surface heat transfer coefficients, Nusselt numbers, and pressure drops, using ANSYS Fluent models. As compared with smooth channel heat sink Nusselt number of 9, the average increase in Nusselt number for RRRG and RRTG is 46 and 36, respectively. The average pressure drops for RRRG and RRTG is higher than smooth channel heat sink by 56 and 35, respectively. As opposed to a smooth channel heat sink, the average thermal enhancement efficiency for RRRG and RRTG is 22 % and 12 % higher, respectively. The results suggest that the geometric arrangement of rectangular ribs and grooves greatly enhances heat transfer by increasing turbulence and disrupting the thermal boundary layer. These findings provide significant insights for the advancement of battery cooling systems, contributing to the reduction of thermal runaway dangers and prolonging battery lifespan.